Acute Disseminated Encephalomyelitis Presenting as Bilateral Ptosis in a Sri Lankan Child. (8th February 2022) - Kumarasiri, Ishara; Samararathna, Ruwan; Sandakelum, Udara; Muthukumarana, Oshanie; Balasubramaniam, Reha; Mettananda, Sachith
Abstract : Introduction . Acute disseminated encephalomyelitis is a rare inflammatory demyelinating disease characterized by acute onset polyfocal neurological deficits associated with encephalopathy. It commonly presents with fever, meningism, seizures, ataxia, motor deficits, and bladder dysfunction. Although cranial neuropathies, including optic neuritis and facial nerve palsies, have previously been reported, children presenting with bilateral ptosis is extremely rare. Here, we report a 3-year-old child with acute disseminated encephalomyelitis presenting with acute onset bilateral ptosis due to involvement of the single central levator subnucleus of the oculomotor nerve. Case Presentation . A 3-year-old Sri Lankan boy presented with drooping of the upper eyelids for three days and unsteady gait for two days. He did not have seizures, blurring of vision, limb weakness, swallowing or breathing difficulties, or bladder dysfunction. On examination, he had bilateral ptosis, gait ataxia, and dysmetria. His vision, eye movements, and examination of other cranial nerves were normal. MRI brain revealed high signal intensities involving the subcortical white matter of parietal and occipital lobes, midbrain in the area of single central levator subnucleus of the oculomotor nerve, cerebellar vermis, and right cerebellar hemisphere. Based on the clinical features suggesting polyfocal neurological involvement of the midbrain and cerebellum and characteristic MRI findings, the diagnosis of acute disseminated encephalomyelitis was made. He responded well and rapidly to high-dose intravenous methylprednisolone and showed a complete clinical and radiological recovery. Conclusion . This case report describes a rare presentation of acute disseminated encephalomyelitis, bilateral ptosis due to involvement of the single central levator subnucleus of the oculomotor nerve. It highlights that the presenting manifestations of acute disseminated encephalomyelitis can be subtle and vary; however, timely diagnosis and treatment result in complete recovery.